2020
DOI: 10.3389/fmicb.2020.01369
|View full text |Cite
|
Sign up to set email alerts
|

Nitrospina-Like Bacteria Are Potential Mercury Methylators in the Mesopelagic Zone in the East China Sea

Abstract: In natural environments, the production of neurotoxic and bioaccumulative methylmercury (MeHg) is mediated by microorganisms carrying the genes hgcA and hgcB . However, the contribution of these microorganisms to mercury (Hg) methylation or MeHg accumulation in the ocean is poorly understood. Here we determined the total Hg (THg) and MeHg concentrations in seawater samples and conducted a metagenomic survey of the hgcAB genes and functional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 81 publications
2
34
0
Order By: Relevance
“…Our results thus suggest that Hg methylation is not linked to iron-reduction in the Baltic Sea. Recent studies also identified hgcAB -carrying Nitrospirea/Nitrospinae from several environments including marine systems ( Gionfriddo et al, 2016 ; Tada et al, 2020 ; Villar et al, 2020 ). Despite members of this genus having been detected in open ocean and seas, we did not find any hgcAB -like genes related to Nitrospina sp.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our results thus suggest that Hg methylation is not linked to iron-reduction in the Baltic Sea. Recent studies also identified hgcAB -carrying Nitrospirea/Nitrospinae from several environments including marine systems ( Gionfriddo et al, 2016 ; Tada et al, 2020 ; Villar et al, 2020 ). Despite members of this genus having been detected in open ocean and seas, we did not find any hgcAB -like genes related to Nitrospina sp.…”
Section: Discussionmentioning
confidence: 98%
“… Podar et al (2015) only detected hgcAB genes in a few metagenomes from marine pelagic waters (seven out of 138 metagenomes) but highlighted that limited sequencing depths of these metagenomes could have hampered detection. While a more recent study did not detect hgcA genes in waters from the Arctic and equatorial Pacific Oceans ( Bowman et al, 2019 ), the presence of hgcAB -like genes was reported in normoxic water from the open ocean in several ocean basins ( Villar et al, 2020 ), the mesopelagic zone of the East China Sea ( Tada et al, 2020 ) and Antarctica sea ice ( Gionfriddo et al, 2016 ), with a fraction of those genes being associated to a microaerophilic nitrite oxidizing bacteria. Further, Blum et al (2013) demonstrated that between 20 and 40 % of MeHg measured in surface mixed layer of the North Pacific Ocean originated from internal production in the surface water.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…These microorganisms are ubiquitous in soils, sediments, seawater, freshwater, and extreme environments, as well as the digestive tracts of some animals [ 9 ]. A few other hgc carriers, not only from anaerobic but also microaerobic habitats, were discovered using culture-independent approaches, including Chloroflexi, Chrysiogenetes, Spirochaetes [ 9 ] , Nitrospina [ 11 , 12 ], and Verrucomicrobia [ 13 ]. Two more recent studies have expanded the Hg-methylating community [ 14 , 15 ] and revealed the role played by Hg methylators in the context of global biogeochemical cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the vertical and horizontal distribution of Hg and MeHg in marine environments is critical for understanding MeHg accumulation in marine organisms. Ocean-scale surveys of Hg distribution have highlighted the abundance of MeHg in the mesopelagic layers ( 2 5 ). In addition, incubation studies have shown the possibility of MeHg production in seawater columns ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%